Correction: Breaking the spiral of silence: News and social media dynamics on sexual abuse scandal in the Japanese entertainment industry. - Tsukasa Tanihara; Mitsuki Irihara; Taichi Murayama; Mitsuo Yoshida; Fujio Toriumi; Kunihiro Miyazaki (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0306104.].